Program Peningkatan Pengetahuan Ibu Nifas terhadap Pemberian ASI Eksklusif di Kelurahan Tenda - Lega, Marelda Vianney; Kusung, Kristina Sindi; Alfionita, Lidia; Anila, Maria; Mensa, Maria Alfini; Tolitorice, Lidia; Kiru, Lidia Faskalina; Setiawan, Maria B. T; Riani, Lusiana Fianilia; Trisnawati, Reineldis E. (Pakis Journal Institute, 2025)
This community service program aims to broaden the insight of postpartum mothers regarding the importance of exclusive breastfeeding. This event was carried out through a seminar held on April 14, 2025 in Tenda Village, involving 15 postpartum mothers as participants. The method used was face-to-face counseling using leaflets containing information on the benefits, techniques for giving, and the significance of exclusive breastfeeding during the first six months of the baby’s life. The results of this activity showed an increase in understanding of postpartum mothers regarding the importance of exclusive breastfeeding after counseling. This activity is expected to be able to encourage better exclusive breastfeeding practices in the community and have a positive effect on the health of mothers and babies.